Exit Options and the Allocation of Authority - Helmut Bester; Daniel Krähmer (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
We analyze the optimal allocation of authority in an organization whose members have conflicting preferences. One party has decision-relevant private information, and the party who obtains authority decides in a self-interested way. As a novel element in the literature on decision rights, we consider exit option contracts: the party without decision rights is entitled to prematurely terminate the relation after the other party's choice. We show that under such a contract it is always optimal to assign authority to the informed and not to the uninformed party, irrespective of the parties' conflict of interest. Indeed, the first-best efficient solution can be obtained by such a contract.
urn:nbn:de:bvb:19-epub-15342-9
Keywords: D23; D82; D86; 330; Authority; decision rights; exit options; incomplete contracts; asymmetric information